2018
DOI: 10.14214/sf.10034
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of provenance and slow-release fertilizer on nursery and field performance of yellowhorn seedlings

Abstract: Yellowhorn ( Bunge) has been widely planted for biodiesel production in China, but has frequently shown poor field performance. Container-grown yellowhorn seedlings originating from three Chinese provenances, Wengniute Qi (WQ), Alukeerqin Qi (AQ), and Shanxian (SX), were fertilized with slow-release fertilizer (SRF) at 40, 80, 120, 160 or 200 mg N seedling. Tree growth, survival and nutrient content were measured after one year’s growth in a greenhouse followed by two years in a field site. Plants from AQ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…This condition indicated that P2 was more responsive in diameter growth to the addition of a dose of NPK fertilizer compared to P1. According to [20], a significant interaction between provenance and NPK fertilization occurred in the N content of the Yellowhorn stem (Xanthoceras sorbifolium Bunge). The addition of NPK fertilization doses also increased the P content of the root and stem of the seedling significantly.…”
Section: Diametermentioning
confidence: 99%
“…This condition indicated that P2 was more responsive in diameter growth to the addition of a dose of NPK fertilizer compared to P1. According to [20], a significant interaction between provenance and NPK fertilization occurred in the N content of the Yellowhorn stem (Xanthoceras sorbifolium Bunge). The addition of NPK fertilization doses also increased the P content of the root and stem of the seedling significantly.…”
Section: Diametermentioning
confidence: 99%
“…Controlledrelease fertilizers (CRF) have been described as an alternative to conventional fertilizers for fertilization of seedlings in the nursery phase, because they induce rapid initial growth (Wang et al, 2016;AO et al, 2018;Shi et al, 2019) and favor sur vival and vigor after the field planting phase (Fu et al, 2017;Shi et al, 2019). Currently, research has shown a positive effect of controlledrelease fertiliz ers on the production of native seedlings in northern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers have also shown the strong positive relationship between increased nutrient reserves in plants fertilized with nutrient solution and survival and vigor after transplanting the seedlings into the field (SHI et al, 2019), even in adverse edaphoclimatic conditions and limiting factors (AO et al, 2018), a reflex is attributed to the accumulation of nutrients in the nursery phase, which would represent an advantage to growth in the postplanting period.…”
Section: Introductionmentioning
confidence: 99%